The influence of profitability, size, and growth on the capital structure in consumer goods companies - Yovilanda Anggraeni Puspitasari; Diah Ekaningtias (STIE Perbanas Surabaya, 2017)
Capital structure is a very important element needed by companies to conduct the com-panies’ operational activities. Companies must determine whether to use internal funds first or external funds to finance investment in getting an optimal capital structure. The purpose of this study is to examine the influence of the variables of profitability, size and growth on the capital structure in consumer goods companies. Multiple regression anal-ysis is used to analyze the data in this study. Data analysis is conducted on consumer goods companies listed on the Indonesia Stock Exchange period 2012-2016. Based on the analysis, it is found that profitability, size, and growth have an effect on capital structure in consumer goods companies listed on the Indonesia Stock Exchange 2012-2016.